Effects of dam milk yield and milk composition on birth weight and growth performance of Anatolian buffalo calves - Akkulak, Özlem; Kul, Ertuğrul (Buffalo Bulletin, 2023)
This study was conducted to determine the effects of the dam’s milk yield and composition on birth weight, 6-month, and 12-month live weight (LW) of Anatolian buffalo calves born in 2017 and 2018 years in Çorum province, Türkiye. Calving age had a significant impact on daily milk yield (DMY) (P=0.031), lactation milk yield (LMY) (P=0.048) and solids-not-fat (SNF) (P=0.034). DMY (P=0.022) and fat content (P=0.005) were affacted by calving season. Suckling period and calf sex had no significant impact (P>0.05) on DMY, LMY, fat content, and solids-not-fat (SNF) (P>0.05). The dam’s calving age had a significant impact on birth weight (P=0.029), except for 6-month and 12-month live weight (LW). Calving season affected 6-month (P=0.002) and 12-month LW (P=0.012) without birth weight. The suckling period and calf sex were not significantly affected on the birth weight, 6-month, and 12-month LWs (P>0.05). The highest 6-month LW (P=0.025) was determined in the calves of high DMY buffaloes (>6.50 kg). The DMY of the dam had no effect on the birth weight and 12-month LWs (P>0.05). The calves of buffaloes with the highest LMY (>1300 kg) were observed the highest birth weight (P=0.040) and 6-month LW (P=0.046). The dam’s fat and SNF content had no effect on the birth weight, 6-month, and 12-month LWs. To conclude; “higher milk yield resulted in higher birth weight” means that better dams give better calves, suggesting that buffalo keepers should feed buffalo cows sufficiently to get heavier calves at least.